Growing trees with sequential redirection - Oviedo, Martina Guadalupe (2019)
A model for growing trees is introduced where nodes receive new links through some redirection process. When a new node enters the network it connects to a randomly selected node, then, after flipping a biased coin, it could stay there or go to its ancestor, and the process is repeated up to c times.